Motivations and Expectations for Pursuing Graduate Education in Mathematics and Science Education - Kurnaz, Mehmet Altan; İncikabı, Lütfi; Pektaş, Murat; Özgelen, Sinan (Anthropologist, 16(3): 701-709 (2013), 2013)
The aim of this study was to reveal the reasons behind the decisions of individuals for pursuing graduate education in mathematics and science education. In this paper, candidates were investigated in terms of their explanations for the necessities of graduate education, their motivational factors for pursuing higher education and their expectations from it. Being qualitative in nature this study was a case study and the case being examined was graduate candidates’ motivations for and expectations from graduate education. The sample consisted of 49 graduate candidates (teachers and recent college graduates) applying to a university in Turkey. Among the results of the study were that graduate candidates’ explanations for necessities for graduate education were mainly gathered under themes of academic development, professional development and social development; that the same themes were also found in their expectations from graduate education; that motivations were consisted of internal and external motivation factors; and that motivations generally caused academic expectations, especially ISCSR and PAS.
Keywords: KEYWORDS Motivation. Expectation. Graduate Education. Mathematics Education. Science Education